Peningkatan Kapasitas Mekanisme Perlindungan Diri Jurnalis Melalui Pelatihan Dasar Keamanan Holistik di Kabupaten Sikka - Rini Kartini; Aurelius Rofinus Lolong Teluma; Angelina Debby Barus; Intan Musthafa (Jurnal Gema Ngabdi, 2023)
The journalist profession is one of the professions that are vulnerable to personal security and safety. In recent years, threats and attacks, even killing journalists, have increased, including in Sikka Regency. This community service aims to encourage the achievement of increasing the basic capacity of journalists, especially in building self-protection mechanisms on the Internet. The methods given are in the form of lectures, sharing experiences, simulations, practice, and discussions. This training was attended by 10 journalists in Sikka Regency. From this training, it is known that all training participants have experienced violence in carrying out their journalistic work, whether physical, verbal, psychosocial or digital violence. The perpetrators of this violence come from the government, the community, sources, fellow journalists, and even the media where journalists work. This is due to journalists' lack of understanding of security itself and is exacerbated by the absence of a Standard Operation Procedure (SOP) at work. This shows that journalists work without being equipped with self-protection capabilities and without protection from institutions. This training is important considering that press freedom is one of the benchmarks for the quality of democracy in a country. This training then initiated the formation of the Safe Sikka Journalist Group.